Bicyclo[6.3.0]undecapentaenyl Anion: The Next Higher Homolog of the Indenyl Anion with Exceptionally Large Ion‐Pairing Effects on its Tropicity. Issue 3 (2nd December 2013) - Ozoe, Hiroaki; Uno, Yasutaka; Kitamura, Chitoshi; Kurata, Hiroyuki; Oda, Masaji; Jones, John W.; Scott, Lawrence T.; Kawase, Takeshi
Abstract The title anion 1 was generated as a fairly thermally stable species in tetrahydrofuran (THF) and dimethylsulfoxide (DMSO) by the action of several bases (sodium hydride, potassium hydride, lithium diisopropylamide, and lithium hexamethyldisilazide) with appropriate bicyclo[6.3.0]undecapentaenes. Variable‐temperature 1H NMR spectra of 1⋅Li+ in [D8]THF reveal that the anion exhibits exceptionally large ion‐pairing effects; proton chemical shifts vary by more than 1 ppm as a function of ion‐pairing conditions. Thus, anion 1, in a contact ion pair (Li+ at ambient temperature in THF), behaves as an aromatic cyclopentadienyl anion that is perturbed only slightly by the electronic effects of a paramagnetic cyclooctatetraene (COT), whereas 1 in a separated ion pair (Li+ at low temperatures in THF or at ambient temperature in DMSO) behaves as an overall paratropic species with a 12 π‐electron periphery. 13C NMR spectroscopy indicates no major skeletal rearrangement and only small variations of the electron density. The variable tropicity of 1 can be ascribed to small conformational changes of the molecule. In addition to its unusual, tunable tropicity, anion 1 can also serve as a versatile building block for the synthesis of cyclopentanoid conjugated systems fused to a fully unsaturated eight‐membered ring. A theoretical calculation predicts that the 10‐position of 1 should have the highest electron density. In agreement with this prediction, the reactions of 1 with electrophiles occur predominantly at the 10‐position. The corresponding ferrocene, two fulvenes, two diazo derivatives, and a COT‐fused azulene were obtained by the reactions of 1 with appropriate electrophiles.